Communication patterns in nurse-led chemotherapy clinics: A mixed-method study. Issue 8 (August 2020) - Farrell, Carole; Chan, E Angela; Siouta, Eleni; Walshe, Catherine; Molassiotis, Alex
Highlights: Nurses were more able to attend to patients' verbal cues of their needs for information than patients' cues for psychosocial issues. Long consultation time with patients has no impact on how nurses respond to patients' verbal cues and concerns. Priorities for medical information and clinical tasks may reduce nurses' focus on psychosocial support. Continuity of care was important for nurses although patient care was sometimes fragmented. Abstract: Objective: To determine patterns of nurse-patient communication in fulfilling patients' informational/psychosocial needs, effects of longer consultation/operational aspects on person-centred care experiences. Methods: Mixed-method design; secondary analysis of transcripts of nurse-patient communication within nurse-led chemotherapy clinics in UK [3 ]. Purposive sampling (13 nurses); non-participant observations (61 consultations). Qualitative content analysis of audio-recorded transcripts. Quantitative analysis using the Medical Interview Aural Rating Scale [14 ] to compare mean differences in the number of cues and level of responding using one-way ANOVA, and correlational analyses of discursive spaces. Results: Nurses responded positively to informational cues, but not psychosocial cues. Longer consultations associated with more informational and psychosocial cues ( p < .0001), but not nurses' cue-responding behaviours. Four main themes emerged: challenges/opportunities for person-centred communication in biomedical contexts; patients' "life world" versus the "medical world"; three-way communication: nurse, patient and family; implications of continuity of care. Conclusions: The challenges/opportunities for cue-responding in nurse-led chemotherapy clinics were evident for informational and psychosocial support of patients. Shifting from a biomedical to biopsychosocial focus is difficult. Practice implications: Further evaluation is needed to integrate biopsychosocial elements into communication education/training. Careful planning is required to ensure continuity and effective use of time for person-centred care.